A study on cold formed steel compression member - a review. (2021) - Kaleeswaran, C.; Saravanakumar, R.; Vivek, D.; Elango, K.S.; Gopi, R.; Balaji, D.
Abstract: Cold Formed Steel (CFS) is a structural or non structural member is used in various construction activities. The behaviour and buckling capacities of cold formed steel as a compression member is assessed from many momentous research articles. The buckling capacities from theoretical and numerical analysis are predicted by AISI, AS/NZ standard and Euro standards. The various types of section like single channel section, back to back channel section (for formation of I-section) and front to front channel section (for formation of Box section) as a compression element is analysed by various researchers. The support condition selected for analysed is pinned or fixed type. Material properties such as yield stress, ultimate stress and young's modulus using of tensile coupon test were premeditated. The experimental test results which are derived theoretical are compared with the numerical analysis generally carried out using ABACUS or ANSYS software. This type of analysis aids in cost reduction for production and material usage which would pave a path to sustainable development.